Utilisation of Resin Materials for Making Souvenir Accessories in Training Activities in Samaan Village, Klojen District, Malang City - Sharf, Oely Maqwa; Sifa, Miftachus; Muhammad , Haitsam (Universitas Muhammadiyah Sidoarjo, 2024)
This activity aims to increase creativity and produce marketable products amid the proliferation of MSMEs in Indonesia. The Community Service Programme, which targets women entrepreneurs in the home industry, is carried out by providing training in the skills of making accessory hangers using resin mixed with a catalyst. The objective of this training is to expand knowledge about the resin-based souvenir production process, as well as introduce and train participants in the production techniques. The steps taken include design preparation, coordination with participants, souvenir design, training implementation, and direct training application to the community, particularly residents of RW 04, Samaan Village. This activity is expected to enhance the residents' ability to use graphic techniques with resin and catalyst materials by adopting cloning or duplication techniques, where an object is replicated as a model. The goal is to produce a product that is not only aesthetically pleasing but also resembles the original object in terms of shape, resulting in high-quality resin keychain souvenirs suitable for marketing. Highlights: Skill Enhancement – Trains women in resin-based souvenir making. Creative Duplication – Uses cloning techniques for quality keychains. Market Readiness – Aims to produce aesthetic, sellable products. Keywords: utilisation of resin, cloning of accessories, souvenirs, women empowerment, duplication technique